PARTICIPATION OF THE PROSECUTION IN THE CONSIDERATION OF CASES ON ADMINISTRATIVE OFFENCES: ON THE ISSUE OF ON THE ENFORCEMENT OF THE JUDGMENT OF THE EUROPEAN COURT OF HUMAN RIGHTS IN THE CASE OF BANTYSH AND OTHERS V. UKRAINE - Sopilko, Iryna; Tarasenko, Yuriy (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2024)
The purpose of the article is to substantiate the approach to regulating the participation of the prosecution in administrative offence cases, which arises from the need to implement the Judgment of the European Court of Human Rights in the case of Bantysh and Others v. Ukraine The need to update the Code of Ukraine on Administrative Offences is evidenced by the ECHR Judgment in the case of Bantysh and Others v. Ukraine of 6 October 2022. Results: the expediency of conducting theoretical and legal studies devoted to the inclusion of the prosecution as subjects of proceedings in cases of administrative offenses is indicated. Proposals for amendments to the Code of Ukraine on Administrative Offenses based on the results of such research are indicated. In particular, it is proposed to single out a separate structural component of the Code of Administrative Offenses, in which to provide for articles defining the concept of prosecution in proceedings in the case of an administrative offense, as well as a list of persons who are parties to the prosecution; to provide for the participation of the prosecutor as a party to the prosecution in cases of administrative offenses, which are considered by a court (judge) in a subordinate department; it is stated, in the order of discussion, that persons who must draw up protocols on administrative offenses and the whistleblower (in the case of consideration of a case on an administrative offense related to corruption) are referred to the prosecution side. Discussion: the article examines the question of the expediency of regulating the participation of the prosecution during the consideration of cases of administrative offenses, which arises from the need to implement the Decision of the European Court of Human Rights in the case of bantysh and others v. Ukraine.